Studi In Silico pada Ekstrak Buah Andaliman (Zanthoxylum acanthopodium DC.) Menghambat α-Amylase sebagai Antidiabetes - Rani, Rada; Amelia, Fitri; Rahmayani, Sherly (Departemen Kimia FMIPA UNP, 2025)
DM is a metabolic disorder characterized by chronic high blood glucose levels that can cause death. Long-term hyperglycemia can slowly cause retinopathy, heart and blood vessel disease, and neuropathy. Andaliman is known to be used as an anti-diabetic because it contains flavonoids, terpenes, and essential oils that are effective in lowering blood glucose levels. This study aims to test the potential for inhibition of the α-amylase enzyme using the molecular docking method. The study was conducted by utilizing a protein that has PDB ID 2QV4 to interact with active compounds in the ethanol extract of andaliman fruit. The results obtained were that the compounds astragalin, cyclocerine, coribulbine, Kaempferol-3-glucuronide, morin, mururin A, oroxin B, rhamnetin, and pyrocyanidin B7 have good binding ability to α-amylase. Thus, these compounds have the potential as antidiabetics.